Standardizacija prekmurske transkripcije samoglasnikov: študija primera: Mihaela Koletnik, Melita Zemljak Jontes (Stanje in perspektive uporabe govornih virov v raziskavah govora, 2024)
Standardisation of Prekmurje Dialectal Transcription of Vowels: a Case Study. In the context of the pilot research of the Prekmurje dialect, this paper examines the suitability of the process of standardisation of Slovene dialectal transcription, where we will (1) analyse the phonetic transcription of the Prekmurje dialectal material for SLA for issln. *, issln. *- and issln. *-; (2) compare the phonetic transcription in the dialectological literature and the accessible material of individual regional centres; (3) perform an acoustic analysis of the accessible audio recordings based on selected examples (experimental phonetic analysis).